2021
DOI: 10.3390/pharmacy10010003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Facilitated Interactive E-Learning for Patients Newly Initiated on Warfarin: A Randomised Controlled Study

Abstract: It is not known whether electronic-learning (e-learning) is effective for educating hospital inpatients about complex medications such as warfarin. This prospective randomised controlled study compared pharmacist-facilitated e-learning with standard pharmacist-delivered face-to-face education on patients’ or their unpaid carers’ knowledge of warfarin and satisfaction with warfarin education as well as the time that was spent by pharmacists in delivering warfarin education. Adult English-speaking patients (or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Globally, 39 papers and 1 report were selected: PubMed (n = 33) [ 10 , 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], SciELO (n = 1) [ 52 ], Google Scholar (n = 6) [ 8 , 53 , 54 , 55 , 56 , 57 ], and sites of known international organizations (n = 1) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, 39 papers and 1 report were selected: PubMed (n = 33) [ 10 , 13 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ], SciELO (n = 1) [ 52 ], Google Scholar (n = 6) [ 8 , 53 , 54 , 55 , 56 , 57 ], and sites of known international organizations (n = 1) [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selected publications were classified as follows: 7 reviews [ 8 , 13 , 23 , 41 , 43 , 52 , 53 ]; 31 original research publications [ 10 , 21 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 55 , 56 , 57 ]; 1 commentary [ 47 ]; 1 case study [ 54 ]; 1 report [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…A review of 24 randomized controlled trials assessing multimedia-based medication counseling indicated that this type of service was at least equivalent to other forms of counseling, such as written and face-to-face patient counseling 45 . Furthermore, recent evidence has proposed that individualized video technology consultation with teach-back questions in anticoagulation counseling, such as warfarin which is considered a complex medication, provided similar patient comprehension as standard pharmacists delivered education 46 . It is worth emphasizing that insufficient warfarin education has been shown to be a predictor factor for bleeding complications in patients receiving this inadequate service 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent evidence has proposed that individualized video technology consultation with teach-back questions in anticoagulation counseling, such as warfarin which is considered a complex medication, provided similar patient comprehension as standard pharmacists delivered education 46 . It is worth emphasizing that insufficient warfarin education has been shown to be a predictor factor for bleeding complications in patients receiving this inadequate service 46 . Yet, still many previous studies on multimedia patient education intervention on critical chronic medications were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation